2012
DOI: 10.1103/physreva.85.053402
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent density-functional-theory calculation of high-order-harmonic generation of H2

Abstract: The observation of the isotope effect in the high-order-harmonic generation (HHG) of H 2 presents a challenge for time-dependent density-functional-theory (TDDFT) methods, since this effect is related to the dynamics of the ion created in the tunneling ionization step of HHG and it depends on the harmonic order. As an initial step toward describing this effect within current computational capacity, we benchmark a method in which the nuclear and electronic degrees of freedom are separated and both treated quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…It was shown that this "SFA-phase" formula reproduces the measured D 2 -to-H 2 HHG ratio [41]. It is much less costly to evaluate Eq.…”
Section: The 39-electron-volt Minimum At the Equilibrium Internucmentioning
confidence: 72%
See 2 more Smart Citations
“…It was shown that this "SFA-phase" formula reproduces the measured D 2 -to-H 2 HHG ratio [41]. It is much less costly to evaluate Eq.…”
Section: The 39-electron-volt Minimum At the Equilibrium Internucmentioning
confidence: 72%
“…(12) involves repeatedly solving TDDFT equations for different R values. In recent work on H 2 , the error caused by using the SFA-phase formula is estimated to be within 7% for similar laser parameters [41]. We expect the error in the case of N 2 to be even smaller, because |d(R,ω)| is more flat as a function of R for N 2 than for H 2 due to the flatter I p (R) of N 2 .…”
Section: The 39-electron-volt Minimum At the Equilibrium Internucmentioning
confidence: 80%
See 1 more Smart Citation
“…v σ,l (r,t)P l (z/r), (21) where P l is lth-order Legendre function and z is the z coordinate. Induced potentials v σ,l P l , l = 0,1, .…”
Section: Resultsmentioning
confidence: 99%
“…The quantum action A[ ] has a stationary point at the TD density of the system, and hence from the Euler equation we get the working equations [20,21]. When we project Eq.…”
Section: Introductionmentioning
confidence: 99%